Elementary and intermediate algebra : - Hutchinson, Donald (McGraw-Hill, 2004)
A Unified Text That Serves Your Needs. Most colleges offering elementary and intermediate algebra use two different texts, one for each course. As a result, students may be required to purchase two texts; this can result in a considerable amount of topic overlap. Over the last few years, several publishers have issued "combined" texts that take chapters from two texts and merge them into a single book. This has allowed students to purchase a single text, but it has done little to reduce the overlap. The goal of this author team has been to produce a text that was more than a combined text. They wanted to unify the topics and themes of beginning and intermediate algebra in a fluid, non-repetitive text. We also wanted to produce a text that will prepare students from different mathematical backgrounds for college algebra. We believe we have accomplished our goals. For students entering directly from an arithmetic or pre-algebra course, this is a text that contains all of the material needed to prepare for college algebra. It can be offered in two quarters or in two semesters. The new Review Chapter found between chapters 6 and 7 serves as a mid-book review for students preparing to take a final exam that covers the first seven chapters. Finally, we have produced a text that will accommodate those students placing into the second term of a two-term sequence. Here is where the Review Chapter is most valuable. It gives the students an opportunity to check that they have all of the background required to begin in Chapter 7. If the students struggle with any of the material in the Review Chapter, they are referred to the appropriate section for further review.